European mental health research resources: picture and recommendations of the ROAMER project - Hazo, Jean-Baptiste; Meyer-Lindenberg, Andreas (European neuropsychopharmacology, 2019)
As part of the Roamer project, we sought to have a picture of the available mental health research (MHR) funding, capacity-building and infrastructures resources and to establish consensus-based recommendations that would allow an increase of European MHR resources and enable better use and accessibility to them. The methods fell into three sections (i) a review of the literature, (ii) a mental health-related keywords search within the Cordis®, On-Course® and Meril® databases which contain information on European research funding, training and infrastructures. These reviews provided an overview that was presented to (iii) two experts workshops with 28 participants drawn from academic which identified gaps and produced recommendations. The literature review illustrates the debates in the scientific community on funding, training and infrastructures. The database searches estimated the fraction of health research resources available for mental health. Eight overarching goals for MHR resources were identified by the workshops; each of them was carried out with several practical recommendations. Resources for MHR are scarce considering the burden of mental disorders, the high rate of return of MHR and the under-investment of the field. The recommendations are urgently warranted to increase resources and their optimal access and use.